Reconsidering the Liberal Captivity of American Evangelicalism - Harp, Gillis J. (Christian scholar's review, 2011)
In this essay Gillis J. Harp notes that some American Evangelicals find it difficult to conceive of a species of conservatism that preserves a moral political economy and some notion of a paternalistic state protecting the less fortunate. Yet this is the kind of conservatism that characterized the thinking of one key strand within the larger fabric of historic Evangelicalism. This thread emphasized community and opposed excessive individualism, and it sometimes sought to contain the impact market forces can have on traditional institutions and the poor. Against laissez-faire individualism, these Evangelicals stressed an organic view of the social order, the state as a moral agent, and the importance of mediating institutions such as family and church. Evangelicals have shortchanged themselves by ignoring this part of their past and some reclamation of this historic thread is long overdue. Its recovery could help make Evangelical social thought less indebted to classical liberalism and Enlightenment categories.